Sử dụng công cụ AI để thiết kế học liệu điện tử trong dạy học Ngữ văn ở trường phổ thông - Đặng Thị Ngọc Lan, Đặng Thị Ngọc Lan; Lã Phương Thúy, Lã Phương Thúy (Tạp chí Giáo dục, 2026)
The application of AI in teaching Literature is an inevitable trend but faces a major challenge: how to integrate technology without losing the “literary essence”. Through theoretical research on digital learning materials, the article seeks ways to use AI to innovate teaching methods. AI provides significant benefits in personalizing learning paths and creating dynamic interactive environments, although barriers regarding infrastructure and data security still exist. The study has established and proposed a 5-step process for designing digital learning materials using AI: (1) Analyzing lesson objectives, (2) Analyzing teaching content, (3) Selecting appropriate AI tools, (4) Designing various forms of learning materials (such as interactive lectures, games, videos, and chatbots), and (5) Testing the learning materials. The application of AI is a breakthrough solution that helps enhance the quality of Literature teaching in high schools. Future research directions could focus on evaluating the impact of large language models (LLMs) on critical thinking, or developing evaluation criteria for students' creative products with AI assistance.